Adipose-Derived Mesenchymal Stem Cells in the Use of Cartilage Tissue Engineering: The Need for a Rapid Isolation Procedure - Sam L. Francis; Serena Duchi; Carmine Onofrillo; Claudia Di Bella; Peter F. M. Choong (Stem Cells International)
Mesenchymal stem cells (MSCs) have shown much promise with respect to their use in cartilage tissue engineering. MSCs can be obtained from many different tissue sources. Among these, adipose tissue can provide an abundant source of adipose-derived mesenchymal stem cells (ADMSCs). The infrapatellar fat pad (IFP) is a promising source of ADMSCs with respect to producing a cartilage lineage. Cell isolation protocols to date are time-consuming and follow conservative approaches that rely on a long incubation period of 24–48 hours. The different types of ADMSC isolation techniques used for cartilage repair will be reviewed and compared with the view of developing a rapid one-step isolation protocol that can be applied in the context of a surgical procedure.